Breast lymphoscintigraphy for sentinel node identification in breast cancers with clinically-negative axillary nodes - Namwongprom S. (2014)
Introduction: To analyse and determine the clinical value of lymphoscintigraphy for sentinel lymph node (SLN) localisation in woman undergoing surgery for breast cancer, and evaluate the predictive value of SLN versus axillary lymph node (ALN) status in these patients. Methods: Preoperative breast lymphoscintigraphy was performed in 35 female patients with breast cancer and clinically-negative ALNs. The mean age was 52.8 years (age range 38 to 73 years). The lymphoscintigraphy was performed using 74 MBq of Tc-99m nanocolloid subdermal injection over the tumour. The SLN location was marked on the skin. All patients underwent standard modified radical mastectomy with axillary lymph node dissection (ALND). A comparison of SLN and ALN histopathological results was completed in order to define the means by which the SLN biopsy was able to reflect the final status of ALNs. Results: In 20/35 (57.1 percent) cases, SLNs were visualised in 20-minute dynamic imaging. In 12 patients, SLNs were seen after delayed imaging and/or by repositioning the patient. Overall, the estimated SLN identification rate was 91.4 percent. Of 32 patients in whom SLNs were localised by lymphoscintigraphy, nine were positive for metastatic tumours and the rest were negative for tumour involvement. In four of these nine patients, SLN was the only node that contained metastatic tumour cells while in five patients, an additional concomitant ALN metastasis was detected. In four patients, SLN was negative on frozen section, but skip ALN metastases were noted. Of three patients in which SLNs were not localised by lymphoscintigraphy, two had positive ALNs for tumour cells and the remaining one was negative for tumour involvement. Conclusion: We concluded that SLN localisation using lymphoscintigraphy is an accurate minimally-invasive procedure for staging breast cancer patients with clinically-negative ALNs, and can substantially reduce the morbidity and costs of surgical treatment by avoiding unnecessary ALND in the majority of patients.